A flexible composite polymer electrolyte membrane and preparation method thereof and lithium ion battery
By using a combination of mixed liquid electrolyte, polymer monomer, photoinitiator and nano-inorganic filler in lithium-ion batteries, a composite polymer electrolyte membrane with high ion conductivity and flexibility was prepared, and the machinery in the prior art was solved The poor performance problem has improved the safety of lithium-ion batteries and the suitability of industrial production.
Patent Information
- Application Number
- CN201710740126.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2017-08-25
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2037-08-25
AI Technical Summary
The existing polymer electrolytes have defects in mechanical properties, making it difficult to prepare electrolyte membranes with good flexibility, limiting the application of lithium-ion batteries.
A flexible composite polymer electrolyte membrane is prepared by ultraviolet curing method using a combination of mixed liquid electrolyte, polymer monomer, photoinitiator and nano-inorganic filler to ensure the high ionic conductivity and good mechanical properties of the membrane.
It achieves high ionic conductivity and good flexibility, improves the safety and mechanical properties of lithium-ion batteries, and is suitable for industrial production.
Smart Images

Figure CN107546410B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical materials, and in particular to a flexible composite polymer electrolyte membrane and a preparation method thereof, and a lithium ion battery. Background Art
[0002] As a new type of energy, lithium-ion batteries have the advantages of high operating voltage, light weight, small size, high specific energy and environmental friendliness, and have become an ideal energy source that has been focused on development in recent years. Compared with liquid lithium-ion batteries, polymer lithium-ion batteries have higher specific energy, thinner appearance, higher design flexibility, and no electrolyte leakage, becoming an inevitable trend in the development of lithium-ion batteries in the future.
[0003] The preparation of polymer electrolytes is the core technology of polymer lithium-ion batteries. Therefore, the development of polymer electrolyte preparation technology can promote the advancement of polymer lithium-ion battery technology. At present, polymer electrolytes are mainly divided into: gel polymer electrolytes, pure solid polymer electrolytes and composite polymer electrolytes mixed with inorganic powders. Gel-type polymer electrolytes are mainly composed of polymers, plasticizers and lithium salts. By properly selecting plasticizers and lithium salts, the lithium ion conductivity of the system can be greatly improved. However, the large amount of plasticizers used in the system will cause safety problems similar to those of liquid electrolytes. All-solid-state polymer electrolytes are composed of only polymers and lithium salts. Since no plasticizer is required, the safety problems caused by the addition of plasticizers are avoided. However, the conductivity of the system at room temperature is too low, which prevents their commercial application. Composite polymer electrolytes are polymer electrolytes obtained by blending, plasticizing and incorporating inorganic powders with polymers as monomers. They not only have high ionic conductivity at room temperature, but also have good processing performance and shape stability. At the same time, they not only have the inherent safety of polymer electrolytes, but also can inhibit the growth of lithium dendrites to a certain extent due to the addition of inorganic powders. Therefore, they are the safest electrolyte material among polymer electrolyte materials and also the most promising type of polymer electrolyte.
[0004] There have been many studies on polymer electrolytes. For example, patent CN 101901938A discloses a composite polymer electrolyte and its preparation method and application. The composite polymer electrolyte is a polymer electrolyte in which inorganic oxide hollow microspheres or core-shell composite materials are added to a polymer matrix. Its preparation methods include direct addition method and in-situ polymerization method. Patent CN 102412378A discloses a polymer electrolyte separator, its preparation method and application. The polymer electrolyte separator is made of lithium salt, organic solvent, photosensitive monomer, photoinitiator and nanofiller; its preparation method is: adding lithium salt to organic solvent, magnetic stirring to obtain electrolyte solution; adding photoinitiator to photosensitive monomer, magnetic stirring to obtain blended monomer; adding electrolyte solution and nanofiller to blended monomer, ultrasonic vibration to obtain mixed solution; coating the mixed solution on the surface of release material; irradiating the surface of release material coated with the mixed solution with ultraviolet light to obtain a polymer separator for lithium battery. Patent CN 101517814B discloses a non-aqueous electrolyte, which contains a first acrylate compound containing one or two acryloyl groups; a second acrylate compound containing three or more acryloyl groups; an electrolyte salt and an organic solvent. Also disclosed is an electrode having a coating layer partially or completely formed on its surface, the coating layer comprising: (i) a first acrylate compound containing one or two acryloyl groups in reduced form; and (ii) a second acrylate compound containing three or more acryloyl groups in reduced form. In addition, an electrochemical device comprising a cathode, an anode, a separator and a non-aqueous electrolyte is disclosed.
[0005] Although current polymer electrolytes have improved in ionic conductivity, they generally have the disadvantage of poor mechanical properties. The preparation of electrolytes with good flexibility requires further research. Summary of the invention
[0006] The object of the present invention is to provide a flexible composite polymer electrolyte membrane and a preparation method thereof and a lithium ion battery. The composite polymer electrolyte has not only high ion conductivity but also good flexibility and can be bent arbitrarily.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In one aspect, the present invention provides a method for preparing a flexible composite polymer electrolyte membrane, comprising the following steps:
[0009] 1) Mixing: mixing the liquid electrolyte, polymer monomer, photoinitiator and nano inorganic filler to obtain a uniformly mixed slurry;
[0010] 2) pouring: pouring the slurry in step 1) evenly onto a mold to obtain a wet film with uniform thickness;
[0011] 3) UV curing: placing the wet film in step 2) under a UV lamp until it is completely cured;
[0012] 4) Peeling off: peeling off the cured wet film from the mold to obtain a flexible composite polymer electrolyte membrane;
[0013] The liquid electrolyte consists of a lithium salt and an organic solvent; the polymer monomer is ethoxylated trimethylolpropane triacrylate and / or propoxylated trimethylolpropane triacrylate, the concentration of the lithium salt in the organic solvent is 0.2-2 mol / L, the mass ratio of the polymer monomer to the liquid electrolyte is 40:60-90:10, the mass of the photoinitiator is 0.5%-20% of the mass of the polymer monomer, and the nano inorganic filler accounts for 1%-80% of the total mass of the raw materials.
[0014] When the polymer monomer is a mixture of ethoxylated trimethylolpropane triacrylate (ETPTA) and propoxylated trimethylolpropane triacrylate (TPPTA), the ratio of ethoxylated trimethylolpropane triacrylate (ETPTA) and propoxylated trimethylolpropane triacrylate (TPPTA) is arbitrary. The mass ratio of the polymer monomer to the liquid electrolyte is 40:60-90:10, such as 50:50, 60:40, 65:35, 70:30, 80:20 or 85:15. The present invention uses a trifunctional functional group polymer monomer with high activity, suitable viscosity and excellent solubility, and the prepared electrolyte membrane has good flexibility and low shrinkage.
[0015] The lithium salt is any one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonylimide) (Li(CF3SO2)2N) or lithium bis(oxalatoborate) (LiB(C2O4)2) or a mixture of at least two of them. When the lithium salt is a mixture, the mass ratio of each component in the mixture is arbitrary.
[0016] The organic solvent is a mixture of two or more carbonate solvents, wherein the carbonate solvent is ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) or methyl propyl carbonate (MPC). In the organic solvent mixture, the volume ratio of each component is arbitrary.
[0017] The concentration of the lithium salt in the organic solvent is 0.2-2 mol / L, such as 0.5 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.5 mol / L, 1.7 mol / L or 1.9 mol / L.
[0018] The nano inorganic filler is one of nano aluminum oxide (Al2O3), nano silicon oxide (SiO2), nano titanium oxide (TiO2), nano zirconium oxide (ZrO2), nano magnesium oxide (MgO) or nano ferroferric oxide (Fe3O4) or a mixture of at least two thereof. When the nano inorganic filler is a mixture, the mass ratio of each component in the mixture is arbitrary. The average particle size of the nano inorganic filler is 10-500nm, such as 50nm, 100nm, 150nm, 200nm, 240nm, 280nm, 300nm, 350nm, 400nm or 450nm. The nano inorganic filler accounts for 1%-80% of the total mass of the raw material, such as 5%, 10%, 15%, 25%, 40%, 50%, 60%, 70% or 75%. The nano inorganic filler provided by the present invention has a certain affinity for organic solvents and can therefore stabilize the solvent; the addition of the nano inorganic filler can improve the mechanical properties and thermal stability of the electrolyte membrane; when the prepared electrolyte membrane is used in a lithium ion battery, the nano inorganic filler can inhibit the growth of lithium dendrites, thereby greatly improving the safety of the lithium ion battery.
[0019] The photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP), and the mass of the photoinitiator is 0.5%-20% of the mass of the polymer monomer, such as 0.8%, 1%, 5%, 7%, 10%, 12%, 14%, 16% or 18%. The photoinitiator initiates the polymerization reaction at the initial stage of ultraviolet light irradiation, so that the polymerization of the polymer monomer can be carried out thoroughly.
[0020] The mixing in step 1) is grinding, stirring, ball milling or bead milling, and its main purpose is to mix the raw materials evenly so that the nano inorganic filler is evenly dispersed in the composite polymer electrolyte membrane; step 1) is carried out in a glove box filled with argon.
[0021] The mold of step 2) is engraved with a groove of a certain depth, the shape of the groove is determined according to production needs, such as circular, triangular, quadrilateral, etc., the depth of the groove is 1-500μm, such as 10μm, 50μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm or 450μm. The substrate of the mold is polypropylene (PP) or polyethylene terephthalate (PET).
[0022] The ultraviolet lamp in step 3) is an LED ultraviolet lamp, and the illumination time is 10-300s, such as 20s, 30s, 50s, 60s, 80s, 90s, 100s, 120s, 160s, 180s, 200s, 240s or 280s. The ultraviolet curing conditions have an important influence on the performance of the solid electrolyte. If the irradiation time is too long, the electrolyte membrane will be over-cured, which will reduce the flexibility of the solid electrolyte membrane. If the irradiation time is too short, the solid electrolyte membrane will not be completely cured, making the skeleton of the solid electrolyte membrane unstable, thereby affecting the strength of the solid electrolyte membrane.
[0023] On the other hand, the present invention provides a composite polymer electrolyte membrane prepared by the preparation method as described above, wherein the thickness of the composite polymer electrolyte membrane is 1-500μm, such as 10μm, 50μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm or 450μm.
[0024] The present invention also provides a lithium ion battery, comprising: a positive electrode, a negative electrode and the flexible composite polymer electrolyte membrane as described above, wherein the flexible composite polymer electrolyte membrane is disposed between the positive electrode and the negative electrode. The lithium ion battery uses the composite polymer electrolyte membrane to replace the original electrolyte and the separator, and has a simpler structure and is safer.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The flexible composite polymer electrolyte membrane provided by the present invention has high ionic conductivity, and because the selected polymer monomer has high activity, suitable viscosity and excellent solubility, the electrolyte membrane has good flexibility and low shrinkage, and can be firmly attached to the substrate of the mold;
[0027] (2) The flexible composite polymer electrolyte membrane provided by the present invention has good mechanical properties and thermal stability due to the presence of nano inorganic fillers;
[0028] (3) The lithium-ion battery containing the flexible composite polymer electrolyte membrane provided by the present invention is safer;
[0029] (4) The preparation method of the flexible composite polymer electrolyte membrane provided by the present invention is simple and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention provides a process flow chart for preparing a flexible composite polymer electrolyte membrane.
[0031] Figure 2 It is a schematic structural diagram of the flexible composite polymer electrolyte membrane provided by the present invention.
[0032] Figure 3 It is a schematic diagram of the bending of the flexible composite polymer electrolyte membrane provided by the present invention.
[0033] Figure 4 Schematic diagrams of lithium dendrite growth: a is a schematic diagram of the growth of lithium dendrites in a liquid lithium ion battery; b is a schematic diagram of the growth of lithium dendrites in a composite polymer electrolyte membrane lithium ion battery provided by the present invention.
[0034] Among them, 1, nano inorganic filler; 2, polymer matrix; 3, electrolyte; 4, lithium dendrite; 5, lithium sheet. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0036] like Figure 1 As shown, the preparation process of the flexible composite polymer electrolyte membrane of the present invention includes the following specific steps:
[0037] 1) Mixing: In a glove box filled with argon, weigh the liquid electrolyte, polymerization monomer, photoinitiator and inorganic particles according to the proportion of ingredients, put them into a container in sequence and mix them to obtain a uniformly mixed slurry;
[0038] 2) pouring: pouring the slurry in step 1) evenly onto a mold to obtain a wet film with uniform thickness;
[0039] 3) UV curing: placing the wet film in step 2) under a UV lamp until it is completely cured;
[0040] 4) Peeling off: Peeling off the wet film cured in step 3) from the mold to obtain a flexible composite polymer electrolyte membrane.
[0041] like Figure 2 The figure shows a schematic structural diagram of the flexible composite polymer electrolyte membrane provided by the present invention. It can be seen from the figure that the electrolyte membrane is composed of an inorganic filler 1, a polymer matrix 2 and an electrolyte 3.
[0042] like Figure 3 The figure shows a schematic diagram of the bending of the flexible composite polymer electrolyte membrane provided by the present invention. It can be seen from the figure that the composite polymer electrolyte membrane does not break after being bent, indicating that it has good flexibility.
[0043] like Figure 4 It is a schematic diagram of lithium dendrite growth provided by the present invention. By comparing a and b, it can be seen that the growth of lithium dendrite 4 in the composite polymer electrolyte membrane is inhibited, thereby making the composite polymer electrolyte membrane lithium-ion battery have higher safety.
[0044] Example 1
[0045] The preparation process of the flexible composite polymer electrolyte membrane is as follows:
[0046] 1) Mixing:
[0047] a. In a glove box filled with argon, 3.0 g of ETPTA and 4.5 g of 0.2 mol / L LiPF6 (EC:PC:BC=2:1:4 volume ratio) electrolyte were weighed using an electronic balance, the two were mixed in a beaker, and magnetic stirring was performed to obtain a uniform solution A;
[0048] b. Weigh 0.15 g of HMPP using an electronic balance and add it to the above solution. Continue magnetic stirring to obtain a uniform mixed solution B.
[0049] c. Weigh 6 g of a 1:1 Al2O3 / ZrO2 mixed powder with a particle size of about 100 nm using an electronic balance, mix it with the mixed solution B in a zirconia ball mill, add zirconia balls at a ball-to-material ratio of 10:1, seal the ball mill, remove it from the glove box, and ball mill for 1 h to obtain a uniformly mixed slurry;
[0050] 2) Casting: In a glove box filled with argon, the slurry was uniformly cast into a mold with a PET plate as the substrate and a circular groove with a depth of 200 μm and a diameter of 18 μm, to obtain a wet film with uniform thickness;
[0051] 3) UV curing: The wet film was irradiated under a 200W LED UV lamp for 30 seconds to obtain a completely cured electrolyte membrane;
[0052] 4) Peeling off: Peeling off the completely cured electrolyte membrane from the mold to obtain a flexible composite polymer electrolyte membrane.
[0053] Example 2
[0054] The detailed preparation process of the flexible composite polymer electrolyte membrane is as follows:
[0055] 1) Mixing:
[0056] a. In a glove box filled with argon, 9 g of ETPTA and 9 g of 0.5 mol / L LiB(C2O4)2 (EC:PC = 1:1 volume ratio) electrolyte were weighed using an electronic balance, the two were mixed in a beaker, and magnetic stirring was performed to obtain a uniform solution A;
[0057] b. Weigh 0.15 g of HMPP using an electronic balance and add it to the above solution. Continue magnetic stirring to obtain a uniform mixed solution B.
[0058] c. Weigh 6 g of a mixed powder of Al2O3 / SiO2 / Fe3O4 with a particle size of about 10 nm in a mass ratio of 1:2:1 using an electronic balance, mix it with the mixed solution B in a zirconia ball mill, add zirconia balls at a ball-to-material ratio of 10:1, seal the ball mill, remove it from the glove box, and ball mill for 1 h to obtain a uniformly mixed slurry;
[0059] 2) Casting: In a glove box filled with argon, the slurry was uniformly cast into a mold with a PET plate as the substrate and a circular groove with a depth of 100 μm and a diameter of 18 μm, to obtain a wet film with uniform thickness;
[0060] 3) UV curing: The wet film was irradiated under a 200W LED UV lamp for 30 seconds to obtain a completely cured electrolyte membrane;
[0061] 4) Peeling off: Peeling off the completely cured electrolyte membrane from the mold to obtain a flexible composite polymer electrolyte membrane.
[0062] Example 3
[0063] The detailed preparation process of the flexible composite polymer electrolyte membrane is as follows:
[0064] 1) Mixing:
[0065] a. In a glove box filled with argon, 5 g of ETPTA and 4.5 g of 0.8 mol / L Li(CF3SO2)2N (EC:MPC = 1:5 volume ratio) electrolyte were weighed using an electronic balance, the two were mixed in a beaker, and magnetically stirred for 10 min to obtain a uniform solution A;
[0066] b. Weigh 0.75 g of HMPP using an electronic balance and add it to the above solution, continue magnetic stirring to obtain a uniform mixed solution B;
[0067] c. Weigh 6 g of Fe3O4 powder with a particle size of about 100 nm using an electronic balance, mix it with the mixed solution B in a zirconia ball mill, add zirconia balls at a ball-to-material ratio of 10:1, seal the ball mill, remove it from the glove box, and ball mill for 1 h to obtain a uniformly mixed slurry;
[0068] 2) Casting: In a glove box filled with argon, the slurry was uniformly cast into a mold with a PET plate as the substrate and a circular groove with a depth of 300 μm and a diameter of 18 μm, to obtain a wet film with uniform thickness;
[0069] 3) UV curing: The wet film was irradiated under a 200W LED UV lamp for 10 seconds to obtain a completely cured electrolyte membrane;
[0070] 4) Peeling off: Peeling off the completely cured electrolyte membrane from the mold to obtain a flexible composite polymer electrolyte membrane.
[0071] Example 4
[0072] The detailed preparation process of the flexible composite polymer electrolyte membrane is as follows:
[0073] 1) Mixing:
[0074] a. In a glove box filled with argon, 6 g of TPPTA and 4.5 g of 1 mol / L LiCF3SO3 (EC:PC:EMC=1:2:1 volume ratio) electrolyte were weighed using an electronic balance, the two were mixed in a beaker, and magnetic stirring was performed to obtain a uniform solution A;
[0075] b. Weigh 0.3 g of HMPP using an electronic balance and add it to the above solution, continue magnetic stirring to obtain a uniform mixed solution B;
[0076] c. Weigh 6 g of MgO powder with a particle size of about 50 nm using an electronic balance, mix it with the mixed solution B in a zirconia ball mill, add zirconia balls at a ball-to-material ratio of 10:1, seal the ball mill, remove it from the glove box, and ball mill for 1 h to obtain a uniformly mixed slurry;
[0077] 2) Casting: In a glove box filled with argon, the slurry was uniformly cast into a mold with a PET plate as the substrate and a circular groove with a depth of 50 μm and a diameter of 18 μm, to obtain a wet film with uniform thickness;
[0078] 3) UV curing: The wet film was irradiated under a 200W LED UV lamp for 30 seconds to obtain a completely cured electrolyte membrane;
[0079] 4) Peeling off: Peeling off the completely cured electrolyte membrane from the mold to obtain a flexible composite polymer electrolyte membrane.
[0080] Example 5
[0081] The detailed preparation process of the flexible composite polymer electrolyte membrane is as follows:
[0082] 1) Mixing:
[0083] a. In a glove box filled with argon, 10 g of a mixture of ETPTA and TPPTA in a mass ratio of 2:1 and 4.5 g of 1.2 mol / L LiAsF6 (EC:PC:DEC = 1:1:1 volume ratio) electrolyte were weighed using an electronic balance, the two were mixed in a beaker, and magnetic stirring was performed to obtain a uniform solution A;
[0084] b. Weigh 1.0 g of HMPP using an electronic balance and place it in the above solution, continue magnetic stirring to obtain a uniform mixed solution B;
[0085] c. Weigh 62 g of ZrO2 powder with a particle size of about 100 nm using an electronic balance, mix it with the above-mentioned mixed solution B in a zirconia ball mill, add zirconia balls at a ball-to-material ratio of 10:1, seal the ball mill, remove it from the glove box, and ball mill for 1 h to obtain a uniformly mixed slurry;
[0086] 2) Casting: In a glove box filled with argon, the slurry was uniformly cast into a mold with a PET plate as the substrate and a circular groove with a depth of 500 μm and a diameter of 18 μm, to obtain a wet film with uniform thickness;
[0087] 3) UV curing: The wet film was irradiated under a 200W LED UV lamp for 50 seconds to obtain a completely cured electrolyte membrane;
[0088] 4) Peeling off: Peeling off the completely cured electrolyte membrane from the mold to obtain a flexible composite polymer electrolyte membrane.
[0089] Example 6
[0090] The detailed preparation process of the flexible composite polymer electrolyte membrane is as follows:
[0091] 1) Mixing:
[0092] a. In a glove box filled with argon, 25 g of ETPTA and 4.5 g of 1.8 mol / L LiClO4 (EC:DMC = 1:3 volume ratio) electrolyte were weighed using an electronic balance, the two were mixed in a beaker, and magnetic stirring was performed to obtain a uniform solution A;
[0093] b. Weigh 0.15 g of HMPP using an electronic balance and add it to the above solution. Continue magnetic stirring to obtain a uniform mixed solution B.
[0094] c. Weigh 0.3 g of SiO2 powder with a particle size of 300 nm using an electronic balance, mix it with the above-mentioned mixed solution B in a zirconia ball mill, add zirconia balls at a ball-to-material ratio of 10:1, seal the ball mill, remove it from the glove box, and ball mill for 1 h to obtain a uniformly mixed slurry;
[0095] 2) Casting: In a glove box filled with argon, the slurry was uniformly cast into a mold with a PET plate as the substrate and a circular groove with a depth of 1 μm and a diameter of 18 μm, to obtain a wet film with uniform thickness;
[0096] 3) UV curing: The wet film was irradiated under a 200W LED UV lamp for 100s to obtain a completely cured electrolyte membrane;
[0097] 4) Peeling off: Peeling off the completely cured electrolyte membrane from the mold to obtain a flexible composite polymer electrolyte membrane.
[0098] Example 7
[0099] The detailed preparation process of the flexible composite polymer electrolyte membrane is as follows:
[0100] 1) Mixing:
[0101] a. In a glove box filled with argon, 30 g of ETPTA and 4.5 g of a 1.5 mol / L electrolyte solution of a mixture of LiBF4 and LiClO4 (EC:BC = 1:2 volume ratio) with a mass ratio of 3:1 were weighed using an electronic balance, and the two were mixed in a beaker and stirred magnetically to obtain a uniform solution A;
[0102] b. Weigh 0.15 g of HMPP using an electronic balance and add it to the above solution. Continue magnetic stirring to obtain a uniform mixed solution B.
[0103] c. Weigh 6 g of TiO2 powder with a particle size of 400 nm using an electronic balance, mix it with the mixed solution B in a zirconia ball mill, add zirconia balls at a ball-to-material ratio of 10:1, seal the ball mill, remove it from the glove box, and ball mill for 1 h to obtain a uniformly mixed slurry;
[0104] 2) Casting: In a glove box filled with argon, the slurry was uniformly cast into a mold with a PP plate as the substrate and a circular groove with a depth of 10 μm and a diameter of 18 μm, to obtain a wet film with uniform thickness;
[0105] 3) UV curing: The wet film is irradiated under a 200W LED UV lamp for 200s to obtain a completely cured electrolyte membrane;
[0106] 4) Peeling off: Peeling off the completely cured electrolyte membrane from the mold to obtain a flexible composite polymer electrolyte membrane.
[0107] Example 8
[0108] The detailed preparation process of the flexible composite polymer electrolyte membrane is as follows:
[0109] 1) Mixing:
[0110] a. In a glove box filled with argon, 40.5 g of ETPTA and 4.5 g of 2 mol / L LiPF6 (EC:PC = 1:1 volume ratio) electrolyte were weighed using an electronic balance, the two were mixed in a beaker, and magnetic stirring was performed to obtain a uniform solution A;
[0111] b. Weigh 8.1 g of HMPP using an electronic balance and add it to the above solution. Continue magnetic stirring to obtain a uniform mixed solution B.
[0112] c. Weigh 3 g of Al2O3 powder with a particle size of 500 nm using an electronic balance, mix it with the above-mentioned mixed solution B in a zirconia ball mill, add zirconia balls at a ball-to-material ratio of 10:1, seal the ball mill, remove it from the glove box, and ball mill for 1 h to obtain a uniformly mixed slurry;
[0113] 2) Casting: In a glove box filled with argon, the slurry was uniformly cast into a mold with a PET plate as the substrate and a circular groove with a depth of 150 μm and a diameter of 18 μm, to obtain a wet film with uniform thickness;
[0114] 3) UV curing: The wet film was irradiated under a 200W LED UV lamp for 300s to obtain a completely cured electrolyte membrane;
[0115] 4) Peeling off: Peeling off the completely cured electrolyte membrane from the mold to obtain a flexible composite polymer electrolyte membrane.
[0116] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a flexible composite polymer electrolyte membrane, It is characterized in that The steps include: 1) Mixing: mixing the liquid electrolyte, polymer monomer, photoinitiator and nano inorganic filler to obtain a uniformly mixed slurry; 2) pouring: pouring the slurry in step 1) evenly onto a mold to obtain a wet film with uniform thickness; 3) UV curing: placing the wet film in step 2) under a UV lamp until it is completely cured; 4) Peeling off: peeling off the cured wet film from the mold to obtain a flexible composite polymer electrolyte membrane; The liquid electrolyte consists of a lithium salt and an organic solvent; the polymer monomers are ethoxylated trimethylolpropane triacrylate and propoxylated trimethylolpropane triacrylate, the concentration of the lithium salt in the organic solvent is 0.2-2 mol / L, the mass ratio of the polymer monomer to the liquid electrolyte is 40:60-90:10, the mass of the photoinitiator is 0.5%-20% of the mass of the polymer monomer, and the nano inorganic filler accounts for 1%-80% of the total mass of the raw materials.
2. The preparation method according to claim 1, It is characterized in that The organic solvent is a mixture of two or more carbonate solvents, and the carbonate solvent is ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate or methyl propyl carbonate.
3. The preparation method according to claim 1, It is characterized in that Step 1) The nano inorganic filler is one of nano alumina, nano silicon oxide, nano titanium oxide, nano zirconium oxide, nano magnesium oxide or nano ferrosoferric oxide, or a mixture of at least two of them.
4. The preparation method according to claim 1, It is characterized in that The average particle size of the nano inorganic filler is 10-500nm.
5. The preparation method according to claim 1, It is characterized in that The lithium salt is any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium trifluoromethylsulfonate, lithium bistrifluoromethylsulfonyl imide or lithium bis(trifluoromethyl)sulfonyl imide oxalatoborate or a mixture of at least two thereof.
6. The preparation method according to claim 1, It is characterized in that The photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
7. The preparation method according to claim 1, It is characterized in that The mixing in step 1) is grinding, stirring, ball milling or bead milling.
8. The preparation method according to claim 1, It is characterized in that The step 1) is carried out in a glove box filled with argon.
9. The preparation method according to claim 1, It is characterized in that Step 2) The mold is engraved with a groove of a certain depth, and the base material of the mold is polypropylene or polyethylene terephthalate.
10. The preparation method according to claim 1, It is characterized in that Step 3) The ultraviolet lamp is an LED ultraviolet lamp, and the irradiation time is 10-300s.
11. A composite polymer electrolyte membrane prepared by the preparation method according to any one of claims 1 to 10, It is characterized in that The electrolyte membrane has a thickness of 1-500 μm.
12. A lithium ion battery having the composite polymer electrolyte membrane according to claim 11, It is characterized in that The invention comprises a positive electrode, a negative electrode and the composite polymer electrolyte membrane, wherein the composite polymer electrolyte membrane is arranged between the positive electrode and the negative electrode.
Citation Information
Patent Citations
Non-aqueous electrolyte and electrochemical device comprising the same
CN101517814B
Composite polymer electrolyte, preparation method and application thereof
CN101901938A
Polymer electrolyte isolating membrane, preparation method and use thereof
CN102412378A
